Private Visions : Japanese Video Art in the 1980s. - Nakamura, Keiji (Tokyo : The Japan Foundation, 1990)
Nagata, Osamu ; Shimano, Yoshitaka ; Harada, Daizaburo ; Visual Brains (Sei Kazama, Hatsune Ohtsu) ; Idemitsu, Mako ; Matsumoto, Toshio ; Dumb Type ; Kurotsuka, Naoko ; Imai, Norio ; Sasaki, Naruaki ; Tosa, Naoko ; Saito, Makoto ; Fujihata, Masaki ; Inagaki, Takashi ; Ina, Shinsuke ; Terayama, Shuji / Tanikawa, Shuntaro
Private Visions : Japanese Video Art in the 1980s, The Japan Foundation, 1990. Touring exhibition in Rome, Italy and elsewhere in Europe and the USA.
boek
Keywords: Japan